Seasonal Life Cycle of Linepithema micans (Forel) (Hymenoptera: Formicidae) in Vineyards - Nondillo, A. [UNESP]; Baronio, C. A.; Bernardi, D.; Bueno, O. C. [UNESP]; Botton, M. [UNESP] (Entomological Soc Brasil, 2016)
Linepithema micans (Forel) is considered to be the main ant species responsible for the spread of Eurhizococcus brasiliensis (Wille), a soil scale that damages vine plants in southern Brazil. In this work, the seasonal life cycle of L. micans was evaluated in vineyards to define the most appropriate time for the application of toxic baits for control. Ant nests were transported to the laboratory in plastic bags, and individual ants were separated into groups of eggs, larvae, pupae, workers, males, and queens, recording the number of individuals per colony. The seasonal life cycle of L. micans in the vineyards began in spring with the deposition of eggs by queens. During the warm months of the year (spring and summer), it was possible to observe nests consisting primarily of eggs and pupae. During the autumn and winter months, the colonies were composed predominantly of larvae and a reduction in eggs was observed. Because the main control strategy targets the larval stage of the insect, the application of toxic baits for the control of L. micans must be performed during the winter.
Keywords: Behavior; control; Eurhizococcus brasiliensis; insect interactions; toxic baits